Repeated maternal non-responsiveness to baby's crying during postpartum and infant neuropsychological development: The Japan Environment and Children's Study. (May 2022) - Matsuki, Taro; Ebara, Takeshi; Tamada, Hazuki; Kato, Sayaka; Kaneko, Kayo; Kano, Hirohisa; Matsuzaki, Kazuki; Sato, Hirotaka; Minato, Kyoko; Sugiura-Ogasawara, Mayumi; Saitoh, Shinji; Kamijima, Michihiro; et al.
Abstract: Background: Longitudinal adverse effects of neglect-related behaviors during postpartum, especially repeated maternal non-responsiveness to the crying baby on their neuropsychological developmental trajectory, have not been fully clarified. Objective: This study aimed to examine the association between postpartum maternal neglect-related behaviors and infant neuropsychological outcomes using the Japan Environment and Children's Study (JECS). Participants and setting: JECS data on 100, 286 mother-child pairs were analyzed. Explanatory variables were "frequency of leaving the baby alone at home" (i.e., leaving the baby alone at home) and "frequency of ignoring the baby when he or she cries" (i.e., ignoring the crying baby) at one month postpartum. The outcomes were measured using the Japanese version of the Ages & Stages Questionnaires-Third Edition (J-ASQ-3). Methods: After multiple imputations, logistic regression analysis was performed to evaluate the association between neglect-related behaviors and the J-ASQ-3 domains at each age. Results: The "sometimes or more" group of "ignoring the crying baby" from six months to three years reported relatively consistent significant associations with developmental delay in communication (maximum adjusted odds ratio [aOR]: 1.456, 95% confidence interval [CI]: 1.261–1.682), gross motor (maximum aOR: 1.279, 95% CI: 1.159–1.411), fine motor (maximum aOR: 1.274, 95% CI: 1.113–1.457), problem-solving (maximum aOR: 1.178, 95% CI: 1.104–1.256), and personal-social domains (maximum aOR: 1.326, 95% CI: 1.255–1.402). The adverse effects of "leaving the baby alone at home" disappeared in many domains by the age of one. Conclusions: Repeated maternal non-responsiveness to baby's crying during postpartum may suppress multiple neuropsychological development during early childhood. Highlights: Adverse effects of ignoring the crying baby on development were long-lasting. Adverse effects of leaving the baby alone at home on development were less. Risk factors of frequency of each neglect-related behavior are different.